Export processing zones as catalysts. - JOHANSSON, Helena (1997)
Discusses the lack of export know-how in developing countries, and the role of export processing zones (EPZs) in transmitting ideas between countries. Describes the link between the overall trade strategy and the impact of the export processing zones on total exports, the attributes of a potentially successful EPZ, and the possible impact of EPZs on the host country.